Trust or consequences : build trust today or lose your market tomorrow - Golin, Al, 1929-2017 (American Management Association, 2004)
The recent rash of corporate scandals-and the ensuing financial ruin of companies and their stockholders - proves that even the bluest of blue chip businesses cannot bank on the blind faith of consumers and investors. More than ever, corporations must rebuild, restore, and strengthen bonds of trust. Al Golin has helped create trust strategies for global business leaders including The Walt Disney Company, Hewlett-Packard, McDonald's, Toyota, Owens-Corning, and many others. Trust or Consequences shows what makes such strategies work, and reveals the eye-opening results of a survey of over 700 business professionals. This essential book reveals how to: create an effective trust strategy; determine the impact of trust issues on stakeholders; assess trust-building performance and calculate the difficulty of restoring trust; create a 'trust bank' for saving deposits of good will to draw on as needed. Trust or Consequences offers tools for identifying trust opportunities, as well as numerous inside accounts of trust-building successes and failures by high-profile organizations and leaders. Filled with provocative ideas about why many companies overlook trust issues, Trust or Consequences brings the subject to center stage - where it must remain if companies are to regain stakeholder loyalty and competitive advantage.